Extrinsic role of gibberellin mitigating salinity effect in different rice genotypes - Farooq, Muhammad; Khan, Muhammad Aaqil; Zhao, Dan-Dan; Asif, Saleem; Kim, Eun-Gyeong; Jang, Yoon-Hee; Park, Jae-Ryoung; Lee, In-Jung; Kim, Kyung-Min (Frontiers in Plant Science, 2022)
The overall effects of gibberellic acid (GA3) with NaCl on different rice genotypes are inadequately understood. The present study determines the effect of different GA3 concentrations on the morphophysiological, molecular and biochemical effects of 120 mM NaCl salt stress in rice seedlings. Salt stress reduced germination percentages and seedling growth and decreased bioactive GA content. It also downregulated the relative expression of α-amylase-related genes – OsAmy1A, OsAmy1C, and OsAmy3C in the salt-sensitive IR28 cultivar. Salt stress differentially regulated the expression of GA biosynthetic genes. Salt stress increased antioxidant activity in all rice genotypes tested, except in IR28. GA3 (50 and 100 μM) mitigates the effect of salt stress, rescuing seed germination and growth attributes. GA3 significantly increased bioactive GA content in Nagdong and pokkali (50 µM) and Cheongcheong and IR28 (100 µM) cultivars. The α-amylase genes were also significantly upregulated by GA3. Similarly, GA3 upregulated OsGA2ox1 and OsGA2ox9 expression in the Cheongcheong and salt-sensitive IR28 cultivars. The present study demonstrated that salt stress inactivates bioactive GA – inhibiting germination and seedlings growth – and decreases bioactive GA content and GSH activity in IR28 and Pokkali cultivars. Further, GA3 significantly reversed the effects of 120 mM NaCl salt stress in different rice genotypes.